Intensity of Free-Radical Processes at Local Cold Trauma After Introduction of Extract of Cryopreserved Piglets’ Skin Fragments or Aqueous Colloidal Solution of Fullerene C60 - Vlasov, Oleksandr O.; Kovalov, Gennadiy O. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 167.